TEACHER’S CHALLENGES IN IMPLEMENTATION OF KURIKULUM MERDEKA IN TEACHING ENGLISH AT SENIOR HIGH SCHOOL - Siti Nuradilah; Eka Nurhidayat; Afief Fakhruddin (Cirebon International Conference on Education and Economics Proceeding, 2024)
Teacher encounter numerous challenges when implementing Kurikulum Merdeka in senior high schools, underscoring the complexities and demands of adapting to this new educational framework. This study explores challenges as well as the various solutions teachers employ to address these challenges, focusing on how teacher navigate the implementation of Kurikulum Merdeka in senior high schools. This research Utilize a qualitative method with a case study approach. The instruments used are interviews, observations, and questioners. The results showed that the challenges faced are (1) lack of understanding, (2) difficulty implementing differentiated learning, (3) lack of training, and (4) challenges in implementing P5. On the other hand, the solutions are (1) teachers are still learning about Kurikulum Merdeka, (2) grouping students from 3 aspects (cognitive, affective, psychomotor), (3) conducting training independently at school, (4) extracurricular activities, and character week. In conclusion, there are still many problems that teacher face in implementing Kurikulum Merdeka, so there needs to be a more relevant solution from further research.